Looking forward to an impactful AASW6 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Samuel Baiyeri, PhD student, Department of Crop Science, University of Nigeria, talks on the opportunity as a young person to be part of the conference to work to ensure sustainable Agricultural development The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/